The Effect of Organizational Justice, Compensation, and Work Motivation to Organizational Commitment and Employee Performance at PT. Recruitfirst Indonesia - Prayuda, Bangbang; Herminingsih, Anik (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the effect of organizational justice, compensation and work motivation to organizational commitment and employee performance. With quantitative methods and involving 50 respondents, the study used saturated sampling techniques. Data collection in this study was conducted through a survey using a questionnaire as a survey instrument to respondents. Data analysis was carried out using the Structural Equation Model - Partial Least Square (SEM-PLS). The results of this study indicate if organizational justice has no effect to organizational commitment, compensation has a positive and significant effect to organizational commitment, work motivation has a positive and significant effect to organizational commitment, organizational justice has no effect to employee performance, compensation has a positive and significant effect to employee performance, work motivation has a positive and significant effect on employee performance, organizational commitment has no effect to employee performance.